1998
DOI: 10.1007/s002210050403
|View full text |Cite
|
Sign up to set email alerts
|

Tail and eye movements evoked by electrical microstimulation of the optic tectum in goldfish

Abstract: This work studies the tail and eye co-ordinated movements evoked by the focal electrical stimulation of the tectum in goldfish. The aim of the study is to understand better those tectal sites and mechanisms that either remain functionally unaltered or are adaptively modified across vertebrates. Stimulation was applied in various tectal zones, and the characteristics of evoked tail and eye movements were examined as a function of the stimulation site over tectal surface and the stimulus parameters. Two types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 59 publications
12
90
0
Order By: Relevance
“…The control ablated group captured significantly more paramecia than the bilateral MeLc and MeLr group across the 5 h assay period and was indistinguishable from the unablated group in C. confirms previous electrophysiological and lesioning studies in other vertebrates (Ewert et al, 2001;Lomber et al, 2001;Doubell et al, 2003). For instance, in trout, activation of the tectum elicits orienting movements, the direction and amplitude of which depend on the site of stimulation (Herrero et al, 1998b). However, our study also showed that the tectum is not always necessary for prey consumption, because paramecia numbers still drop at measurable rates in the presence of tectum-ablated (or blind) fish (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…The control ablated group captured significantly more paramecia than the bilateral MeLc and MeLr group across the 5 h assay period and was indistinguishable from the unablated group in C. confirms previous electrophysiological and lesioning studies in other vertebrates (Ewert et al, 2001;Lomber et al, 2001;Doubell et al, 2003). For instance, in trout, activation of the tectum elicits orienting movements, the direction and amplitude of which depend on the site of stimulation (Herrero et al, 1998b). However, our study also showed that the tectum is not always necessary for prey consumption, because paramecia numbers still drop at measurable rates in the presence of tectum-ablated (or blind) fish (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Pretectal nuclei, as well as the optic tectum, have been implicated in the regulation of visual and motor behaviour, multimodal sensory integration [32] and escape responses [33], which may explain the significant increased in subordinates or loser conditions, as observed in the present study. In mammals, avoidance responses are obtained from stimulations in a region of the superior colliculus that appears to represent the upper visual field [34].…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, this nucleus projects to the optic tectum. It is known that the optic tectum is involved in the visual perception of objects and has a role in visually mediated escape responses (Springer et al, 1977;Herrero et al, 1998). Although chemosensory stimuli could modulate visual functions at the level of the optic tectum, we can exclude this explanation for our findings, because destruction of the retinal DA-IPCs and intraocular application of the D2 antagonist sulpiride eliminate the effect of amino acids on visual function.…”
Section: Olfactory Input Modulates Zebrafish Visual Sensitivitymentioning
confidence: 73%